Using Conditional Sentences in Domestic Violence Cases: A New Brunswick Exploration - Gill, Carmen; Thériault, Luc (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2010)
Conditional sentencing was introduced in Canada in 1996 and has since gainedmomentum in the justice system as an alternative to incarceration. The NewBrunswick Advisory Council on the Status of Women (2006) reports a growinguse of conditional sentences in woman abuse cases as well as a decrease in theaverage jail time imposed on convicted abusers. In this article, we explore the useof conditional sentencing in the Province of New Brunswick, comparing domesticviolence cases for which a conditional sentence was issued against a random sampleof domestic violence cases from the year 2004. Key variables examined includedthe nature of the previous criminal record (if any) of the accused, the level ofviolence used, the perception the victim has of her safety, and the relationshipbetween the victim and the accused. Results indicate that none of the selectedvariables had a significant effect on the use of conditional sentencing.La peine avec sursis a Ctk introduite au Canada en 1996; depuis, elle s'estprogressivement imposCe dans le systkme judiciaire comme une alternative 5l'incarc6ration. Le Conseil consultatif sur la condition de la femme du Nouveau-Brunswick (2006) signale un usage croissant des peines avec sursis dans les casde violence contre les femmes ainsi qu'une diminution de la duree moyenne del'incarckration imposee aux agresseurs condamnks. Dans cet article, nous exploronsl'usage de la peine avec sursis dans la province du Nouveau-Brunswick ell comparantles cas de violence domestique recevant une peine avec sursis a un Cchantillonde cas de violence domestiques pris au hasard 2 partir de 2004. Les variables essentiellesexaminees comprennent la nature du casier judiciaire antCc6dent de 1'accusC(s'il y a lieu), la gravitC de la violence utilisee, la perception de la victime quanta sa sCcurit6 et la relation entre la victime et l'accuse. Les rksultats indiquent qu'aucunede ces variables sClectionnCes n'a eu un effet important sur l'usage de la peineavec sursis.